A Study on Correlation of COVID-19 Vaccination and Hospitalization among Adults Aged 45 Years and Above: A Hospital Based Case Control Study - Prakash Patel; Kalpesh Chodvadiya (Medsci Publications, 2021)
Introduction: Year 2020 witness emergence of a pandemic caused by a novel severe acute respiratory syndrome - coronavirus 2 (SARS-CoV-2). After the availability of the vaccine, it is important to assess its effectiveness in reducing morbidity and mortality. The study was conducted to determine the effectiveness of vaccination against severe COVID-19 disease among individuals aged 45 years and above Methodology: The study included patients hospitalized in selected tertiary care hospital and individuals attending SARS-CoV-2 testing facility in the hospital. It was case-control study. Covid19 RTPCR positive cases admitted in hospital were taken as cases and individuals attending the COVID-19 testing facility of hospitals diagnosed negative for SARS-CoV-2 by rRT-PCR were taken as control. The study was done in second quarter of the year 2021. Results: The vaccination was significantly high among controls (63.5%) in comparison to cases (14.5%). This indicates that vaccination has significantly reduces hospitalization. The vaccination has very positive effect in reducing hospitalization (OR 0.1 (0.05-0.2)). Conclusion: Vaccine was very effective in reducing hospitalization due to Covid19. So, this study strongly support vaccination in above 45-year age people.